Eﬀect of energetic incentive of bees with carbohydrates on the 13C isotopic composition of honeys from Uruguay (INNOTEC, 2018)
In the international market, honeys are subjected to a rigorous analytical test that determines their authenticity or their adulteration with artifcial sugars derived from C-4 plants. In case of mishandling of the supply of the energetic incentive, it is possible that the honeys resulted in this authenticity test as adulterated with exogenous sugars. Te objective of this work was to evaluate the incidence of the practice of feeding whit energetic incentive in the analytical test of determination of adulteration by C-4 sugars. For this study honey from 20 apiaries were collected. Te results showed that the apiary-handling carried out according to the standards of good practices of beekeepers are not risk for honey to be classifed as adulterated. However, it was found that in an apiary where bees had an energetic incentive in a not opportune period, the honey resulted in the authenticity proof as adulterated by C-4 sugars. Terefore, it was recommended that the practice of energetic incentive be carried out only in moments of food shortage for the bees, so that they do not collect the same food, and the analytical controls demonstrate the high quality standard of Uruguayan honeys.
Keywords: honey; C-4 sugar adulteration; 13C